2017
DOI: 10.14417/ap.1142
|View full text |Cite
|
Sign up to set email alerts
|

O suporte social e a personalidade são significativos para os objetivos de vida de adolescentes de diferentes configurações familiares?

Abstract: O suporte social tem vindo a ser evidenciado na literatura pela sua relevância no que concerne à planificação e estabelecimento de objetivos de vida de jovens adolescentes. Vivências emocionais adversas no contexto familiar, nomeadamente perdas significativas e transições podem, todavia, condicionar este processo. A presente investigação objetiva analisar o papel do suporte social no desenvolvimento de objetivos de vida de jovens de diferentes configurações familiares (famílias tradicionais e jovens em acolhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(65 reference statements)
0
5
0
4
Order By: Relevance
“…The presence of attachment relationships based on high levels of avoidance seem to reduce the attribution of importance to intrinsic life aspirations. Adolescents in RC who maintain quality affectional bonds, associated with secure attachment, more easily develop positive internal models, which lead to the construction of intrinsic life aspirations (Bronfenbrenner, 1979;Mota & Oliveira, 2017). The literature has suggested that relationships established with significant figures in RC could be particularly relevant to respond to psychological needs, namely definition of life goals, plans and future guidelines (Cuevas et al, 2017;Mota & Matos, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of attachment relationships based on high levels of avoidance seem to reduce the attribution of importance to intrinsic life aspirations. Adolescents in RC who maintain quality affectional bonds, associated with secure attachment, more easily develop positive internal models, which lead to the construction of intrinsic life aspirations (Bronfenbrenner, 1979;Mota & Oliveira, 2017). The literature has suggested that relationships established with significant figures in RC could be particularly relevant to respond to psychological needs, namely definition of life goals, plans and future guidelines (Cuevas et al, 2017;Mota & Matos, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has suggested that relationships established with significant figures in RC could be particularly relevant to respond to psychological needs, namely definition of life goals, plans and future guidelines (Cuevas et al, 2017;Mota & Matos, 2015). On the other hand, the RC process tends to trigger feelings of loss and difficulties in establishing significant affectional relationships (with avoidance organization), resulting in a weaker definition of future goals (Mota & Oliveira, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations